Educar para incluir: Estratégias e desafios na educação de jovens e adultos frente às barreiras atitudinais e sociais - (:unkn) unknown (Universidade Federal do Pampa, 2026)
This research addresses school inclusion in Youth and Adult Education (EJA), discussing its relevance not only for the reintegration of students in this modality to complete elementary school, but also for the need to promote civic inclusion, outlining strategies to overcome challenges related to attitudinal and social barriers faced by students. The study discusses the following theoretical-conceptual axes: Youth and Adult Education; inclusion as a civic theme; inclusion as a fundamental human right; challenges and opportunities for inclusion in the EJA context; and the attitudinal barriers observed in daily school life. The objective of the research is to contribute to the development of youth and adult education, focusing on overcoming attitudinal barriers, inclusion, awareness-raising, and the civic education of students, aiming for a society without discrimination. This is qualitative, ethnographic research that uses the researcher's class diaries as the primary data collection instrument (André, 2008), accompanied by direct field immersion/observation, covering the classroom context and the teaching-learning process in the citizenship subject and interdisciplinary classes. The subjects involved were 10 EJA students from a municipal school in Bagé (RS) during the second semester of 2024. The methodological path consisted of analyzing students' perceptions regarding pedagogical practices to promote school inclusion, considering the identification and overcoming of attitudinal and social barriers. In addition to the class diaries, a questionnaire was administered (November 2025) to identify participants' perceptions before and after the educational intervention. Data analysis, carried out through complementary instruments, identified barriers such as: racism, aporophobia, ageism, social exclusion, classism, sexism, ableism, LGBTphobia, school stigmatization, and educational inequalities. The research contributes to the EJA field by highlighting barriers that compromise civic education and the full social inclusion of students.
Educating for inclusion strategies and challenges in youth and adult education in the face of attitudinal and social barriers
Keywords: Inclusão; EJA; Cidadania; Barreiras atitudinais; Inclusion; Youth and Adult Education (EJA); Citizenship; Attitudinal barriers; CIENCIAS HUMANAS